GREEN BEAN (Phaseolus vulgaris L.) AGRO-PRODUCTIVE RESPONSE TO THE APPLICATION OF LIXIVIATE VERMICOMPOST AND EFFICIENT MICROORGANISMS - Hurtado, Alexander Calero [UNESP]; Díaz, Yanery Pérez; Hurtado, Yainier González-Pardo; Simón, Lesly Analay Yanes; Viciedo, Dilier Olivera; Calzada, Kolima Peña; Rodríguez, Jorge Félix Meléndrez (Universidad Nacional de Colombia, 2020)
With the objective of to evaluate the green bean agro-productive response to the application of lixiviate vermicompost (VL) and efficient microorganisms (ME) bioproducts under organoponic conditions. An experiment was conducted in the organoponic El Estadio, of February to May 2013. The sowing of the variety Verlili was executed at the distance of 80 cm between lines and 20 cm between plants. The treatments were distributed in random blocks, in a factorial scheme (2 x 2), evaluating the absence and presence (100 mL L ') of the leached vermicompost and the efficient microorganisms bioproducts, respectively. At 35 days after emergency, the plant height and average of leaves per plant was determined, and from the 42 days after emergence in five harvests the number of legumes, length and mass of the fruits, as well as the yield were evaluated. The results showed that the use of bioproduct efficient microorganisms was superior relative to leached vermicompost bioproduct, which increased morpho-productive indicators and performance. However, the results indicate that the use of both bioproducts constituting an efficient alternative to increase green bean productivity and sustainability under these growing conditions.
RESPUESTA AGROPRODUCTIVA DE LA HABICHUELA(Phaseolus vulgaris L.) A LA APLICACIÓN DE VERMICOMPOST LIXIVIADO Y MICROORGANISMOS EFICIENTES
Keywords: beneficial microorganism; foliar application; lixiviate humus; soil inoculation